Healing our autistic children : a medical plan for restoring your child's health - Buckley, Julie A. 4 0 16; Vannucci, Lynn; 5 (New York : Palgrave Macmillan, 2010)
Julie A. Buckley argues autism is a physiological disease that can be medically treated, describes her personal experiences with her autistic daughter, and provides information for parents on alternative treatment options and dietary advice.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Diet therapy.;Alternative treatment.;Diet therapy.;Alternative treatment. -- Autism in children;Autism in children;Autism;Autism; 20; 2